Acts of dramaturgy : the Shakespeare trilogy - Pinchbeck, Michael (ISSN., 2020)
The three playtexts from the touring project The Trilogy, inspired by Shakespeare, together with essays reflecting on the politics of dramaturgy, authorship, adaptation, text and performance in contemporary theatre. An important and highly original contribution to the growing interest in interdisciplinary practice research. 12 col. illus.